Biosynthesis of Isoleucine and Valine in Rhodopseudomonas spheroides: Regulation of Threonine Deaminase Activity - Barritt, G. J. (1971)
The activities of threonine deaminase, acetohydroxy acid synthetase, acetohydroxy acid reductoisomerase, dihydroxy acid dehydrase, and transaminase B were detected in cell-free extracts of Rhodopseudomonas spheroides. No significant repression or derepression of threonine deaminase activity was observed.